Intruder in a two-dimensional granular system: effects of dynamic and static basal friction on stick-slip and clogging dynamics - Carlevaro, Manuel; Kozlowski, Ryan; Pugnaloni, Luis; Zheng, Hu; Socolar, Joshua E. S.; Kondic, Lou (My University, 2019)
We discuss the results of simulations of an intruder pulled through a two-dimensional granular system by a spring, using a model designed to lend insight into the experimental findings described by Kozlowski et al. [Phys. Rev. E 100, 032905 (2019)]. In that previous study the presence of basal friction between the grains and the base was observed to change the intruder dynamics from clogging to stick–slip. Here we first show that our simulation results are in excellent agreement with the experimental data for a variety of experimentally accessible friction coefficients governing interactions of particles with each other and with boundaries. Then, we use simulations to explore a broader range of parameter space, focusing on the friction between the particles and the base. We consider a range of both static and dynamic basal friction coefficients, which are difficult to vary smoothly in experiments. The simulations show that dynamic friction strongly affects the stick–slip behaviour when the coefficient is decreased below 0.1, while static friction plays only a marginal role in the intruder dynamics.
Keywords: Granular flows; Jamming